2019
DOI: 10.1016/j.dib.2019.104055
|View full text |Cite
|
Sign up to set email alerts
|

The soybean root membrane lipids and forage quality data in response to field cultivation on agricultural podzols in boreal climates

Abstract: The objective of this data in brief article is to represent the associated data set regarding our published paper in Plant Science Nadeem et al., 2019. Data set represent soil acid phosphatase activity, association of individual molecular species of four major lipid classes with soybean forage quality indices when cultivated in boreal podzolic soils under cool climatic conditions. Phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidic acid (PA) and acylated glucosyl betasitosterol ester (AGIcSiE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…In fact, crop varieties are selected based on their resilience and adaptation under different climate zones (Fox et al 2019). Concomitant with genotypic expression, endogenous or induced production of membrane lipids has also been reported to be part of the successful strategy associated with plant acclimation in specialized growth conditions or environments (Nadeem et al 2019b(Nadeem et al , 2019c. Kim et al (2016) demonstrated that different molecular species of triacylglycerol, phosphatidylglycerol, monogalactosyldiacylglycerol and phosphatidic acid could be used as biomarkers to discriminate Panax ginseng L. cultivars, as well as their cultivation age.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, crop varieties are selected based on their resilience and adaptation under different climate zones (Fox et al 2019). Concomitant with genotypic expression, endogenous or induced production of membrane lipids has also been reported to be part of the successful strategy associated with plant acclimation in specialized growth conditions or environments (Nadeem et al 2019b(Nadeem et al , 2019c. Kim et al (2016) demonstrated that different molecular species of triacylglycerol, phosphatidylglycerol, monogalactosyldiacylglycerol and phosphatidic acid could be used as biomarkers to discriminate Panax ginseng L. cultivars, as well as their cultivation age.…”
Section: Introductionmentioning
confidence: 99%
“…Authors further demonstrated that using the predicted model approach, unknown samples of Panax ginseng L. could be successfully identified. Our previous work has also demonstrated that membrane lipids in soybean are crucial in determining plants' ability to adapt to different environmental conditions (low pH and cool climate) in boreal climate (Nadeem et al 2019b(Nadeem et al , 2019c. Herein, we are interested to explore whether root membrane lipids could be used as suitable biochemical markers to discriminate different silage-corn genotypes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations